ANALISIS MANFAAT EKONOMI DAN NON EKONOMI KOPERASI PERIKANAN ISM MITRA KARYA BAHARI - Niken Wiandhani; Dyah Aring Hepiana Lestari; Achdiansyah Soelaiman (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
The purpose of this research are: (1) analyze the cooperative’s economic advantage for members, (2) analyze the cooperative’s non economic advantage for members. This research was taken at ISM Mitra Karya Bahari Cooperative in Kota Karang East Teluk Betung Bandar Lampung city which has been chosen purposively. Data of this research was collected on February 2015 – March 2015 using survey method. Total respondents were 50 members of cooperative, consist of fish processor, product derived processor, fishermen and labor. Respondents were taken by simple random sampling method. Data was analyzed descriptively by Importance-Performance Analysis. Result of this research showed that: (1) the economic advantage was received by members in the form of cash, which were net income and economic advantage calculated by the service cost of selling and purchasing. Total average economic advantage of cooperative’s members were product derived processor (Rp400.490,00), fish processor (Rp267.236,84), fishermen (Rp193.668,75) and labors (Rp150.500,00). (2) The non economic advantage which was satisfaction need to be improved. Satisfaction level of the members on RAT service and unit business utilization was on high category (satisfied), but satisfaction level of payment of compulsory savings was on low category (less satisfied). Key words: advantage, cooperative, member satisfaction